Coupling-inspired metasurfaces for polarization-correlation customizable absorption. (24th September 2021) - Li, Yongfeng; Pang, Yongqiang; Zheng, Lin; Chen, Hongya; Feng, Mingde; Wang, Jiafu; Zhang, Jieqiu; Qu, Shaobo
Abstract: Polarization-correlation customizable metasurface absorbers based on circular dichroism (CD) meta-atoms were proposed in this paper, of which the polarization-correlation can be altered by controlling the coupling effect between the CD meta-atoms with the same chirality. CD meta-atoms implemented via introducing resistance film into chiral resonators were firstly proposed. Wideband, high-efficiency left-handed/right-handed CD meta-atoms were demonstrated, respectively, for which the left-handed/right-handed circularly polarized (LCP/RCP) incident wave was strongly absorbed but the RCP/LCP incident wave was reflected into LCP/RCP wave with high efficiency. The metasurface absorber consisting of CD-meta-atom pairs were put forward for polarization-correlation customizable absorption. The coupling between two CD meta-atoms was investigated by theoretical and simulation analysis, which can be manipulated by controlling the orientation angles of the CD meta-atoms. As a proof-of-concept, a polarization-insensitive absorber utilizing a C4 2 × 2 CD-meta-atom pair was designed, simulated and measured. Attributed to the strong coupling between the four CD meta-atoms, both LCP and RCP wave were strongly absorbed in a wide frequency range from 8 GHz to 20 GHz. This paves a new way for designing wideband metasurfaces with polarization-correlation customizable performance.